Merancang Masa Depan: Meningkatkan Motivasi Siswa SMK 2 Pasundan Tasikmalaya Untuk Melanjutkan Pendidikan - Hania Windi Rohmah Febrianti; Jilda Permata Nur Aliya; Imas Hena Crisye Nurfalah; Eka Rahmawati; Nafiisah Humaira Khalisha; Aditya Jaya Permana; Muslim Haidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Higher education plays an important role in improving the quality of human resources and preparing the younger generation to face global challenges. However, many high school students are still hesitant to continue their studies to higher education due to limited information, economic factors, lack of motivation, and minimal environmental support. This activity aimed to improve students’ understanding and motivation to pursue higher education through a counseling program. The implementation method used a participatory descriptive approach conducted at SMKN 2 Pasundan Tasikmalaya in April 2026, involving 21 students from grades X, XI, and XII. The activity was carried out in three stages: needs analysis, program implementation, and evaluation. The methods used included lectures and Focus Group Discussion (FGD). The results showed an increase in participants’ knowledge regarding the importance of higher education, university admission pathways, job opportunities, and educational assistance programs such as KIP Kuliah and scholarships. In addition, there was an increase in students’ active participation during discussions, changes in perceptions regarding tuition costs, and stronger interest in continuing their studies to a higher level. The main obstacles expressed by participants included economic factors, lack of family support, and limited information. Overall, the counseling program had a positive impact in improving students’ understanding, motivation, and future orientation toward continuing education.